VeryFastCCD: a high frame rate soft X-ray detector - Goldschmidt, Azriel; Grace, Carl; Joseph, John; Krieger, Amanda; Tindall, Craig; Denes, Peter (Frontiers in Physics, 2023)
Direct X-ray detection in silicon has been transformative for scattering experiments in biology and materials science. While bump-bonded hybrid pixels have been attractive for hard X-ray detection, the challenge for single photon soft X-ray detection is sufficiently low noise. CCD structures on thick, high-resistivity silicon have been successfully used as sensors over the range of soft to hard Xrays at storage rings and FELs. The VeryFastCCD is a high frame rate, column-parallel CCD sensor with 48 m pixels. Combined with 256-channel custom readout ASICs, frame rates of 5-10 kHz have been achieved with readout noise as low as 20 e-and full-well capacity >4x10 5 e-/pixel. Thin (10 nm and 100 nm) entrance window contact processes have also been developed which provide >85% quantum efficiency for 285 eV X-rays. Systems are currently being developed for several beamlines at the upgraded Advanced Light Source.